2020
DOI: 10.1177/1470785320972526
|View full text |Cite
|
Sign up to set email alerts
|

Predicting online shopping cart abandonment with machine learning approaches

Abstract: Excessive online shopping cart abandonment rates constitute a major challenge for e-commerce companies and can inhibit their success within their competitive environment. Simultaneously, the emergence of the Internet’s commercial usage results in steadily growing volumes of data about consumers’ online behavior. Thus, data-driven methods are needed to extract valuable knowledge from such big data to automatically identify online shopping cart abandoners. Hence, this contribution analyzes clickstream data of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
(110 reference statements)
0
11
0
2
Order By: Relevance
“…effective to be abandoned shopping cart. Overall, their findings showed that device used for online shopping can also affect purchasing behavior (Rausch et al, 2020).…”
Section: Riskmentioning
confidence: 99%
“…effective to be abandoned shopping cart. Overall, their findings showed that device used for online shopping can also affect purchasing behavior (Rausch et al, 2020).…”
Section: Riskmentioning
confidence: 99%
“…Recency (Meier, 2012), (Chen et al, 2012), (Mesforoush & Tarokh, 2013), (Danaee et al, 2013), (Tsai et al, 2013), (Zhang & Wang, 2014), (Sauro, 2015), (Hosseini & Mohammadzadeh, 2016), (Rezaeian et al, 2016), (Carnein & Trautmann, 2019), (Anitha & Patil, 2019) Frequency (Meier, 2012), (Chen et al, 2012), (Danaee et al, 2013), (Mesforoush & Tarokh, 2013), (Tsai et al, 2013), (Zhang & Wang, 2014), (Sauro, 2015), (Hosseini & Mohammadzadeh, 2016), (Rezaeian et al, 2016), (Aziz, 2017), (Dullaghan & Rozaki, 2017), (Anitha & Patil, 2019) Monetary (Meier, 2012), (Chen et al, 2012), (Tsai et al, 2013), (Mesforoush & Tarokh, 2013), (Danaee et al, 2013) (Hosseini & Mohammadzadeh, 2016), (Rezaeian et al, 2016), (Dullaghan & Rozaki, 2017), (Carnein & Trautmann, 2019), (Anitha & Patil, 2019) Demographic characteristics (Yadav et al, 2012), (Sauro, 2015), (Dullaghan & Rozaki, 2017), (Rausch et al, 2022) Page view (Meier, 2012), (Zhang & Wang, 2014),…”
Section: Attribute Studymentioning
confidence: 99%
“…In this work, in order to predict the segments of the customers, we use classification algorithms namely; Logistic Regression (LR), Support Vector Machines (SVM), Multi Layer Perceptron (MLP), Naive Bayes (NB), K-Nearest Neighbor (KNN) and Decision Tree (DT) algorithms. (Kotsiantis, Zaharakis, & Pintelas, 2007) makes a comprehensive review of the supervised classification algorithms and Hosseini & Mohammadzadeh, 2016; Xiao, Cao, Jiang, Gu, & Xie, 2017; Won, Kim, & Ahn, 2018; Qian, Tong, & Wang, 2019; Rausch, Derra, & Wolf, 2022) use these algorithms in CRM problems. Beside these base classifiers, we also utilize the well known ensemble methods, namely Adaboost (AB), Bagging (BG) and Random Forest (RF).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yinelemeli Sinir Ağları tabanlı sınıflandırıcıların diğer yöntemlere göre daha başarılı olduğu görülmüştür. Rausch, Derra, & Wolf (2020) internetten alışveriş yapan bireylerden alışveriş sepetini terk edenleri makine öğrenmesi yöntemleri ile belirlemiştir. Gradient Boost (with regularization) yöntemi ile kurulan modelin en iyi doğruluk değeri elde ettiği görülmüştür.…”
Section: Introductionunclassified